PENGEMBANGAN ALAT PERMAINAN KOTAK ALFABET UNTUK MENGENAL HURUF PADA KELOMPOK B DI TK AL PIKRI BOJONGMANGU - Aisyah; Erna Budiarti (Jurnal Tumbuh Kembang Anak Usia Dini, 2024)
This study aims to develop an educational game tool, the alphabet box, to help Group B children at TK Al Pikri Bojongmangu recognize letters. Early childhood has unique characteristics and requires positive stimulation for the development of various aspects, including language development. Language development in children is very important as it is a tool for thinking, self-expression, and communication. The research method used is research and development (R&D) with both qualitative and quantitative approaches. The development process of this game tool involves several stages, starting from needs analysis, design, prototyping, to testing and evaluation. Data were collected through observations, interviews, and questionnaires given to teachers and children at TK Al Pikri Bojongmangu. The results of the study show that the alphabet box is effective in improving children's ability to recognize letters. Children become more interested and motivated to learn letters through this game. Teachers also responded positively to the use of this tool in the learning process. The conclusion of this study is that the alphabet box can be an effective and enjoyable tool for letter recognition for early childhood. The use of educational game tools like this can optimally support children's language development.